Assessing Alternative Modifications to the Affordable Care Act Impact on Individual Market Premiums and Insurance Coverage - Eibner, Christine (RAND Corporation, 2014)
This report summarizes analysis in which the COMPARE microsimulation model was used to estimate how several potential changes to the Affordable Care Act, including eliminating the individual mandate and eliminating the law's tax-credit subsidies, might affect 2015 individual market premiums and overall insurance coverage. The report also presents estimate how changes in young adult enrollment might affect 2015 individual market premiums.